2014
DOI: 10.1186/1754-6834-7-90
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of magnetic nanoparticle immobilised cellulases in enhancing enzymatic saccharification of pretreated hemp biomass

Abstract: BackgroundPrevious research focused on pretreatment of biomass, production of fermentable sugars and their consumption to produce ethanol. The main goal of the work was to economise the production process cost of fermentable sugars. Therefore, the objective of the present work was to investigate enzyme hydrolysis of microcrystalline cellulose and hemp hurds (natural cellulosic substrate) using free and immobilised enzymes. Cellulase from Trichoderma reesei was immobilised on an activated magnetic support by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(91 citation statements)
references
References 42 publications
7
83
1
Order By: Relevance
“…enzyme was observed at pH 5.0; a similar pH profile has been reported for the immobilization of bgl on iron magnetic nanoparticles (Abraham et al, 2014), while other studies demonstrated that immobilized bgl on magnetic nanoparticles reaches its maximum activity at pH 4.0 (Ahmed et al, 2013;Zhou et al, 2013). In most cases, the immobilized bgl was found to keep its activity in a pH range from 2.5 to 5.0, indicating that the immobilized enzyme is less sensitive to the modification of the pH than the free enzyme.…”
Section: Effect Of Temperature and Ph On The Activity Of Immobilized Bglsupporting
confidence: 55%
See 1 more Smart Citation
“…enzyme was observed at pH 5.0; a similar pH profile has been reported for the immobilization of bgl on iron magnetic nanoparticles (Abraham et al, 2014), while other studies demonstrated that immobilized bgl on magnetic nanoparticles reaches its maximum activity at pH 4.0 (Ahmed et al, 2013;Zhou et al, 2013). In most cases, the immobilized bgl was found to keep its activity in a pH range from 2.5 to 5.0, indicating that the immobilized enzyme is less sensitive to the modification of the pH than the free enzyme.…”
Section: Effect Of Temperature and Ph On The Activity Of Immobilized Bglsupporting
confidence: 55%
“…The high surface area of GO leads to specific interactions with the enzyme, which may induce conformational changes in the protein, leading to an increased hydrolytic activity (Serefoglou et al, 2008;Patila et al, 2013). Moreover, the small size of iron nanoparticles, as well as their high specific surface area, increases the flexibility of the enzyme, which in turn induces a high hydrolytic activity (Abraham et al, 2014). This specific combination of interactions with the protein molecules probably does not occur for bgl/γFe alone or for bgl/GO-C 2 -NH 2 , where the activity of bgl is consequently lower.…”
Section: Immobilization Yield and Activity Of Immobilized Bglmentioning
confidence: 99%
“…Compared to other pretreatment methods, by now, this pretreatment method is close to practical application in industrial production due to low chemical cost and utilization with diverse biomass feedstocks including hardwood and agricultural residues (Benjamin et al, 2013;Mesa et al, 2017). Typically, pretreated biomass is then subjected to enzymatic hydrolysis to produce glucose via a mixture of enzymes such as endoglucanase (EG), exoglucanase or cellobiohydrolases (CBHs), and β-glucosidase (Abraham et al, 2014). CBHs are a group of cellulases that can hydrolyze glycosidic linkages at a crystalline surface of cellulose (Igarashi et al, 2009).…”
mentioning
confidence: 99%
“…Various inexpensive carbon sources, such as whey from the dairy industry, processed fruit pulp from the food processing industry (an important resource for recovering nutrients), bread and bakery waste, 20 crude glycerol, 14 oil cake, lignocellulose resource 21 and molasses can be tested for growing novel microalgal strains 22 . Such cost-effective carbon sources may lead to higher or comparative yield to glucose and glycerol, thus decreasing upstream processing costs.…”
Section: Future Perspectivesmentioning
confidence: 99%